(untitled) (Research, Society and Development, 2021)
Tooth bleaching has become the first clinical option in reversing chromatic changes. This study evaluated the efficiency of four different approaches for home-based chemically induced tooth whitening. 32 patients were randomly distributed into four groups (n=8), according to the bleaching technique performed: G1: control group – at-home dental bleaching with 10% carbamide peroxide (Whiteness Perfect/FGM) delivered in a customized tray, G2: teeth whitening pen containing hydrogen peroxide (Walgreens), G3: night-time whitening gel (CVS) containing hydrogen peroxide and G4: whitening strips (3D White Oral B) containing 10% hydrogen peroxide. Chromatic changes (ΔE) were collected at baseline and at the middle and end of the treatment, using a digital spectrophotometer (EasyShade – Vita). Tooth sensitivity, gingival irritation, and degree of satisfaction were also recorded. The comparison between the average ΔE means, considering the final and initial values, revealed a statistically significant difference between the results obtained by G1 (ΔE2=11.65) and the other groups (ΔE2 of G2=4.38, G3=4.83 and G4 = 8.32). No significant difference was observed in the occurrence of tooth sensitivity and gingival irritation. The patients from G1 and G4 were more satisfied with the treatment outcome.